1998
DOI: 10.1007/s004170050043
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive assay for the quantification of glucose and lactate in the human cornea using a modified bioluminescence technique

Abstract: The modified bioluminescence technique provides a highly sensitive quantification of glucose and lactate in the human cornea and thus reveals more details of the overall metabolic status of the tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Shortly after the alkali burn the lactate concentration in cornea is, however, expected to decrease due to a lower glycolytic activity [19]. In control eyes the concentrations of lactate and glucose in the cornea were found to correspond well with those reported recently in fresh human corneas [8].…”
Section: Discussionsupporting
confidence: 79%
“…Shortly after the alkali burn the lactate concentration in cornea is, however, expected to decrease due to a lower glycolytic activity [19]. In control eyes the concentrations of lactate and glucose in the cornea were found to correspond well with those reported recently in fresh human corneas [8].…”
Section: Discussionsupporting
confidence: 79%
“…This trend has been reported previously, with glucose ranges of 0.0043 to 0.094 mmol/L observed in the tear film. [18][19][20][24][25][26][27][28]30 In this study, a few tear glucose concentrations were observed at the 5.6 mmol/L level; the majority of tear glucose values, even after the glucose challenge, remained below 0.56 mmol/L. We have been unable to account for these spuriously high readings.…”
Section: Discussionmentioning
confidence: 90%
“…18,20 The tear glucose values we measured are similar in value and range to those reported previously. [18][19][20][24][25][26][27][28]30 As shown in Figures 1 and 2, the tear glucose values did appear to have a loose relationship with the glucose values observed in the blood for the nondiabetic and diabetic subject populations, respectively. As expected, the blood glucose changes in the diabetic subject group were larger than those observed in the nondiabetic subject group.…”
Section: Discussionmentioning
confidence: 99%
“…While glucose remains mainly outside the cells, lactate is found in the intracellular and extracellular fluid. Both these metabolites can be assayed now with sensitive micromethods (15). Unlike glucose and lactate, ATP and ADP are restricted to cells (Tab.…”
Section: Electrolytes and Metabolites In Corneal Stroma And Epitheliummentioning
confidence: 99%